Elaboración de un plan de negocios aplicando el modelo MyCoop para la Asociación Quindiana de Apicultura para todos beneficiaria de la fundación Fundecompe. (2016)
The following report is about the development of a business plan implementing MyCoop’s model for the Asociación Quindiana de Apicultura para Todos, attached to Fundecompe Foundation. Initially, a socioeconomic diagnosis of the organization was made in order to know its conditions. Thus, we could recognize and focus on the main issue found. Then, the elaboration of the business plan began. It implemented the methodology proposed by The Ministry of Agriculture, MyCoop. This methodology aims to make sure that, a clear and consistent business model that can be able to offer the correct answers to the needs of the company and the trade itself can be developed successfully. Finally, the plan was socialized with the business associates in order to empower the plan itself so they will be able to carry it out and share it with the private and public projects in the city.